Role of Information, Education and Communication (IEC) for HIV/AIDS - Dr. Vinod Kumar (Journal of Advanced Research in Education, 2024)
Today it is impossible to think of life without communication. Human history has passed through different stages of evolution, but the present era is being described as the age of communication. Though communication is as old as human history itself, what is remarkable about the present age is the revolutionary changes in the mode of communication. There is no doubt that human communication consisting of exchange of information existed from the dawn of human civilization. Since then, the method of gathering information and the mode of transmitting the same from place to place and person to person have undergone remarkable changes. Scientific and technological advancement have also made it possible to improve methods of preserving vast quantities of information for use as and when we need them. Today what is being described as the communication revolution deals primarily with Information, Communication Technology (1CT). It affects the way we deal with data and information in three important areas: (a) gathering, (b) transmission (c) storage. The aim of the present research paper is to study the role of Information, Education and Communication for HIV/AIDS.